Neonate with a swelling over the back – Rare bleeding disorder - R. Chidambar; B. K. Praveen; Harsha Prasad Lashkari (Muller Journal of Medical Sciences and Research)
A female baby presented with a swelling over the dorsolumbar region and yellowish discoloration of the skin on day 2 of life. The mother had no comorbidities, normal antenatal scans, no chronic medications, and was born by normal vaginal delivery. The baby had high bilirubin levels, requiring phototherapy. Magnetic resonance imaging showed a cystic lesion in the right paravertebral dorsolumbar region, and a hematoma was confirmed. On day 7 of life, the baby appeared pale with new ecchymosis over the lumbar region with persistent umbilical bleed. A factor XIII (FXIII) test showed clot FXIII deficiency, and fresh frozen plasma transfusion was transfused and recovered well. The baby’s genetic test revealed a homozygous variant in the F13A1 gene associated with FXIII deficiency.